The Role of Phosphorus Slag in Steam-Cured Concrete - Jin Liu; Dongmin Wang (Advances in Materials Science and Engineering)
Steam curing is an effective method to increase the hydration degree of binder containing phosphorus slag. The role of phosphorus slag in steam-cured concrete was investigated by determining the hydration heat, hydration products, nonevaporable water content, pore structure of paste, and the compressive strength and chloride ion permeability of concrete. The results show that elevated steam curing temperature does not lead to new crystalline hydration products of the composite binder containing phosphorus slag. Elevating steam curing temperature enhances the early hydration heat and nonevaporable water content of the binder containing phosphorus slag more significantly than increasing steam curing time, and it also results in higher late-age hydration degree and finer pore structure. For steam-cured concrete containing phosphorus slag, elevating curing temperature from 60°C to 80°C tends to decrease the late-age strength and increase the chloride permeability. However, at constant curing temperature of 60°C, the steam-cured concrete containing phosphorus slag can achieve satisfied demoulding strength and late-age strength and chloride permeability by extending the steam curing duration.